Environmental noise analysis of aged ceramic insulator under influence of electrical stress - Mohd Noor, Mohd Azree (2012)
This thesis mainly presents a study about Corona Discharge that is commonly occurred at Ceramic Insulator surface. The purposed of this research is to study the effect of Corona to the environment in term of the severeness and impact to human and also wildlife using TERCO HV experiment setup and field investigation. These methods have been chosen due to its availability, cost effective and many other reasons. This research is done by analyzing the corona discharge by-product mainly audible noise during the corona event by using Sound Level Meter to obtain the desired data. After the experiment is taken place, the data found reveal the severity of the corona and flashover sound measurement which happen to formed broadband frequency range noise with a very low and high frequency threshold compared to human hearing. The decibel level of when corona occur slightly exceed the comfortable level during daytime which is 60 dB maximum and the value reach to the untolerable level when the flashover is taking place. Magnetic field with a high reading at a very close range is also detected but the value reduced exponentially with distance and leave a harmless exposure at distance more than 8 meter. From the result obtain, corona audible noise is not significantly affect normal people quality of living. However, this does not applied to people with sound sensitivity disorder and remote place which sound different can easily be detected. Low frequency that affect human health is also a thing to be concern with. The recent study does proved the low frequency negative effect to human body to be more than myth while the animal have a tendency to be disturb by high frequency in term of their communication and sensitive hearing. Safety precatious and consideration by authorities before installing high voltage structure can reduced the possibility of living beings are distracted and suffer from the problems discussed.